JavaScript introductory - Gosselin, Don. (Cambridge, Mass. : Course Technology, 2000)
This book presents: Introduction to Java Script; Variables, Functions, Objects, and Events; Data types and Operators; Decision making with control structure and Statements; ...
Keywords: Javascript; Computer program language; JavaScript (Computer program language)